Spectrophotometry of Chromatic Variability in the Rock Paintings of Tecsecocha, Ccorca, Cusco - Carlos Guillermo Vargas Febres; Ana Torres Barchino; Juan Serra; Edwin Roberto Gudiel Rodríguez; Ernesto Favio Salazar Pilares (Arts)
This communication presents an approach to the chromatic study of rock painting scenes in the Tecsecocha sector, Ccorca district, Cusco, Peru, through the application of color spectrophotometry using Capsure by XRite, considered a portable device that facilitates reference measurements of color codes belonging to the visible spectrum (400–700 nm). It is evident that this methodology does not perform the physicochemical characterization of the pigments present in the rock paintings, which are cataloged as artistic heritage of the nation, making it unfeasible to extract physical samples or significantly alter the rock paintings. Therefore, the NCS color notation system allowed for the non-invasive recording of color tones. The results showed a predominance of white and red tones with variations in their shades; among the most frequent codes, S2030-Y70R and S3010-Y40R stand out, indicating yellow tones with red influences of 70% and 40%, respectively. In the anthropomorphic figures, a slight variation in the proportion of red was identified, suggesting differences in the application of pigments, while in the representations of camelids, the tones varied from S3005-Y20R (yellow with 20% red) to S2030-Y70R (greater red influence).